Peer-punishment in a cooperation and a coordination game - Felix Albrecht; Sebastian Kube (Games, 2018)
We elicit individual-level peer-punishment types in a cooperation (social dilemma) and a coordination (weakest link) problem. In line with previous literature, we find heterogeneity in peer-punishment in both environments. Comparing punishment behavior across the two environments within subject, we observe a high degree of individuals' punishment type stability. However, the aggregate punishment demand is higher in the weakest-link game. The difference between the two environments is driven by subjects whose behavioral types are inconsistent rather than by a change in the punishment demand of those who punish in both environments.
Keywords: 330; peer punishment; strategy method; type classification; public goods game; coordination game; weakest link game